Late Mesozoic marine Antarctic fi shes: future perspectives based on the newly collections recovered in the Ameghino and Lopez de Bertodano Formations - Gouiric Cavalli, Soledad; Acosta Burllaile, Leonel Gustavo; Iglesias, Ari; Moly, Juan José; O'gorman, Jose Patricio; Reguero, Marcelo Alfredo; Santillana, Sergio; Talevi, Marianella; Vieytes, Emma Carolina; Bigurrarena Ojeda, Mauricio; Lusky, Jorge
Nowadays, notothenioids are the teleostean group that dominates marine Antarctic waters.However, during the Mesozoic a diverse ichthyofauna inhabited the sea that surrounded Antarctic. Wepresent the preliminary results of the last two Argentinian Antarctic i eld expedition to the LateJurassic of Antactic Peninsula (Longing Gape) and Cretaceous-Paleogene of Seymour (=Marambio)Island. The i sh material recovered is extremely abundant and their further detailed study may providesignii cant clues into the taxonomy and paleobiogeography of the mesozoic antactic ichthyofaunas. Fil: Gouiric Cavalli, Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Acosta Burllaile, Leonel Gustavo. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Iglesias, Ari. Universidad Nacional del Comahue; Argentina Fil: Moly, Juan José. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: O'gorman, Jose Patricio. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Reguero, Marcelo Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Santillana, Sergio. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Talevi, Marianella. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de ...